Predicting nutritional status during pregnancy by women's empowerment in West Shewa Zone, Ethiopia - Etea, Tizita Dengia; Yalew, Alemayehu Worku; Sisay, Mitike Molla; Shiferaw, Solomon (Frontiers in Global Women's Health, 2023)
Background: Considerable proportions of pregnant women are affected by poor nutrition outcomes in Ethiopia. Women’s empowerment, on the other hand, is highly recognized as a means to achieve better maternal nutrition outcomes. However, the role of women’s empowerment on pregnant women’s nutritional status has not been empirically examined and their correlations are not well established in Ethiopia. Objective: To assess the association of individual and composite women’s empowerment dimensions with pregnant women’s nutrition outcomes in West Shewa zone, Ethiopia. Methods: Health facility based cross-sectional study was done among 1,453 pregnant women living in West Shewa zone, Ethiopia in 2021. Exploratory and confirmatory factor analyses were conducted on half of the samples to identify and validate dimensions of women’s empowerment. Logistic regression was conducted to examine the associations between women’s empowerment dimensions and anemia status and mid upper arm circumference (MUAC) level. Results: Composite women’s empowerment was positively associated with both anemia status and MUAC level. The odd of not being anemic was higher among pregnant women empowered in economic [(AOR and 95%CI) =1.7, (1.26, 2.22)] and assertiveness [(AOR and 95%CI) =1.9, (1.46, 2.38)] dimensions compared to those not empowered in these dimensions. Empowered pregnant women in household decision making [(AOR and 95%CI) =1.6, (1.19, 2.22)] and psychological [(AOR and 95%CI) =1.4, (1.04, 1.85)] dimensions had higher odds of having normal MUAC measures compared to those not empowered with the respective dimensions. Communication and time dimensions were not significantly associated with any of the nutrition outcomes. Conclusions: This study suggests that empowered pregnant women are nutritionally better-off than their less empowered counter parts. This is also important in child outcome and child health hence policies and programs that aim in the improvement of maternal and child health need to focus in interventions that promote the decision making power, economic, psychological and assertiveness of pregnant women.